Contrasting formulation in translating French lyrics into English - Severy, Jean (Journal of Modern Languages, 2017)
The following paper analyzes the contrast existing between well-known English songs and their French models both in their formulation and their meaning. Using as a point of departure the original French lyrics, we see, thanks to the translation of their English version back into French, how mood, form and content have been modified to give each song a life and a character of its own.